Efeito das taxas de descarte sobre medidas econômicas de vacas leiteiras em Kentucky - Ribeiro, Anamaria Cândido; McAllister, Alan Jack; Queiroz, Sandra Aidar de [UNESP] (Sociedade Brasileira de Zootecnia, 2003)
Foram utilizadas 19.565 lactações vitalícias de vacas da raça Holandesa para avaliar o impacto dos motivos de descarte sobre a rentabilidade vitalícia de vacas leiteiras, mais especificamente sobre a receita líquida vitalícia (RLV), eficiência vitalícia (EF), receita do leite menos o custo de alimentação (RLMA) e receita líquida por dia de vida produtiva (RLD). A taxa geral de descarte foi igual a 31,39%, valor que pode ser considerado alto e estaria diretamente relacionado com a vida produtiva curta encontrada para estes rebanhos, 25,57 meses. A principal causa de descarte foi problema reprodutivo (21,57%), seguido por injúrias e outras causas (21,17%) e baixa produção (17,20%). Os descartes involuntários foram a grande maioria, representando 75% do total. As diferentes medidas econômicas estudadas sofreram impacto significativo do motivo de descarte, em que as vacas removidas por venda para fins leiteiros foram as mais rentáveis ao produtor.

The aims of this research were to evaluate the effect of culling reasons on lifetime economic measures of dairy cows especially, Lifetime Net Income (LNI), Lifetime efficiency (LE), Income Over Feed Costs (IOFC) and Lifetime income per day of productive life (LIPL) using 19,565 lifetime records from Holstein cows. Culling rate was calculated dividing the number of culled animals, yearly, by the number of all animals present in each year. Data on reasons for disposal were used to calculate the culling rate distribution, dividing the number of animals in each class of culling reason by the total number of animals. The estimated culling rate was 31.39%. This value was high and could be a result from the short productive life of cows, 25.57 months. The main reasons for disposal were reproductive problems (21.57%), injuries and other causes (21.17%), and low production (17.20%). Involuntary culling was responsible for the majority of culling, representing 75% of total. All traits were significantly affected by culling reason. Cows culled for dairy purposes were more profitable to producers.
Effect of culling reasons on lifetime profitability measures of dairy cows in Kentucky
Keywords: Dairy cattle; productive life; profitability; net income; bovinos de leite; Rentabilidade; receita líquida; vida produtiva